Pulmonary hypertension in patients with a history of intravenous drug use. (3rd June 2019) - McGee, Michael; Whitehead, Nicholas; Twaddell, Scott; Collins, Nicholas
Abstract: Objective: Pulmonary hypertension may be a consequence of intrinsic elevation in pulmonary vasculature resistance or complicate numerous other conditions affecting the cardiac and respiratory systems. In this review we sought to explore the relationship between pulmonary hypertension and intravenous drug use. Methods: A narrative review was conducted using PubMed MeSH search with further papers identified using a standard PubMed search with relevant key terms and various synonyms. Results: HIV infection may be associated with pulmonary hypertension due to indirect consequences of viral infection, venous thromboembolism or its therapies. Anti-retroviral infection may also influence plasma concentrations of commonly used treatments for pulmonary hypertension. Intravenous drug use is acknowledged as an important portal for the acquisition of hepatitis virus C infection, with portopulmonary hypertension a potential complication associated with poor prognosis. Interferon based therapy, used in treatment of chronic hepatitis C infection, may also play a causal role in the development of pulmonary hypertension. More recently, sofosbuvir has been linked to development or exacerbation of pulmonary arterial hypertension. Certain drugs of abuse may cause pulmonary hypertension due to properties that result in direct injury to the pulmonary vasculature. The potential for embolic phenomena, complicating venous thromboembolism, recurrent embolization of particulate matter or because of right-sided endocarditis, resulting in pulmonary hypertension is an important contributing factor in the pathophysiology in this unique cohort. Conclusions: Eliciting a history of intravenous drug use is important and may be associated with a number of less common etiologies, each with specific diagnostic and therapeutic implications.